Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Sepeda Motor Pada PT. Alfa Scorpii Medan - Edwin Sugesti Nasution; Muammar Rinaldi (LPPM STIE EKA PRASETYA, 2021)
This study aims to determine the effect of Promotion on Customer Satisfaction at PT. Alfa Scorpii Medan, determine the effect of Service Quality on Customer Satisfaction at PT. Alfa Scorpii Medan, determine the effect of Promotion and Service Quality on Customer Satisfaction at PT. Alfa Scorpii Medan. The population in this study are customers of PT. Alfa Scorpii Medan in 2019 which is 480 customers. By using the Slovin formula with an error rate of 10%, a total sample of 83 respondents was obtained. The results of the research analysis showed that Promotion and Service Quality partially and simultaneously have a positive and significant effect on Customer Satisfaction at PT. Alfa Scorpii Medan. The results of this study are supported by the value of R square (R2) which means that Promotion and Service Quality have an effect on Customer Satisfaction at PT. Alfa Scorpii Medan. While the remaining is effected by other factors originating from outside this research model such as brand trust, brand image, brand association, price, advertising, personal selling, distribution channels and consumer commitment.